Influence of the intermittent vibration ratio on the electro-osmotic consolidation of dredged sludge. Issue 3 (4th March 2023) - Zhang, Dikang; Xu, Jing; Fu, Hongtao; Li, Xiaobing; Cai, Ying; Hu, Xiuqing
Abstract: During electroosmosis experiments, the electrical interface resistance between electrodes increases with soil cracking, which hinders the further improvement of electroosmosis efficiency. To improve the effectiveness of later stage electroosmosis, the consolidation effect of dredged sludge was studied using electroosmosis combined with excitation loading. In this study, a series of experimental tests were used to analyze the influence of the intermittent vibration ratio on the consolidation effect of sludge. The electric current, effective potential, drainage, surface settlement, water content and undrained shear strength were monitored during sludge improvement. After testing, it was concluded that compared with the pure electro-osmotic method, the consolidation effect of the electro-osmotic method combined with the excitation loading method had significant performance improvements on the soil. In addition, the optimal intermittent vibration ratio was obtained, which could provide a design basis for engineering practice.